Long‐term efficacy and safety of cannabidiol in patients with treatment‐resistant epilepsies: Four‐year results from the expanded access program. Issue 3 (10th January 2023) - Szaflarski, Jerzy P.; Devinsky, Orrin; Lopez, Merrick; Park, Yong D.; Zentil, Pilar Pichon; Patel, Anup D.; Thiele, Elizabeth A.; Wechsler, Robert T.; Checketts, Daniel; Sahebkar, Farhad
Abstract: Objective: Cannabidiol (CBD) expanded access program, initiated in 2014, provided add‐on CBD to patients with treatment‐resistant epilepsies (TREs) at 35 US epilepsy centers. Prior publications reported results through December 2016; herein, we present efficacy and safety results through January 2019. Methods: Patients received plant‐derived highly purified CBD (Epidiolex®; 100 mg/ml oral solution), increasing from 2 to 10 mg/kg/day to tolerance or maximum 25–50 mg/kg/day dose, depending on the study site. Efficacy endpoints included percentage change from baseline in median monthly convulsive and total seizure frequency and ≥50%, ≥75%, and 100% responder rates across 12‐week visit windows for up to 192 weeks. Adverse events (AEs) were documented at each visit. Results: Of 892 patients in the safety analysis set, 322 (36%) withdrew; lack of efficacy (19%) and AEs (7%) were the most commonly reported primary reasons for withdrawal. Median (range) age was 11.8 years (range = 0–74.5), and patients were taking a median of three (range = 0–10) antiseizure medications (ASMs) at baseline; the most common ASMs were clobazam (47%), levetiracetam (34%), and valproate (28%). Median top CBD dose was 25 mg/kg/day; median exposure duration was 694 days. Median percentage reduction from baseline ranged 50%–67% for convulsive seizures and 46%–66% for total seizures. Convulsive seizure responder rates (≥50%, ≥75%, and 100% reduction) ranged 51%–59%, 33%–42%, and 11%–17% of patients across visit windows, respectively. AEs were reported in 88% of patients and serious AEs in 41%; 8% withdrew because of an AE. There were 20 deaths during the study deemed unrelated to treatment by the investigator. The most common AEs (≥20% of patients) were diarrhea (33%), seizure (24%), and somnolence (23%). Significance: Add‐on CBD was associated with sustained seizure reduction up to 192 weeks with an acceptable safety profile and can be used for long‐term treatment of TREs.